Feasibility Study of Investment Development Of a Clean Water Supply System for Increasing Water Source Discharge - Hardi, Edelbertus Lusius; Witjaksana, Budi; Patriadi, Andi (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
The availability of clean water is a complex and urgent problem. Water is a natural resource that is very important for human survival. The problem faced is that the clean water system in the area where residents live is not running smoothly. To overcome this, a good clean water distribution network and good clean water system management are needed and are able to serve the clean water needs of residents in the area. In order to make this happen, quite a large investment is needed. One of them is by carrying out company investment in the form of increasing the capacity of the raw water supply system. Based on the background mentioned, the title of this research is Feasibility Analysis of Investment in the Clean Water System of the Wae Mbeliling Drinking Water Company, Lembor District. The settlement method for this calculation is for Feasibility Investment Analysis using the Net Present Value (NPV) method and the Break Event Point (BEP) method. From the results of the analysis, an NPV value of Rp. 678,904,405,208 (NPV > 0). So the investment in developing the production capacity and clean water network of Perumda Air Minum Wae Mbeliling, Lembor District, is worth continuing. An NPV value that is positive or greater than (> 0) indicates that the income is greater than the value invested. It was found that the return value occurred in the 4th year by marking the accumulation of positive profits starting from the 4th year. This explains that the investment in replacing the clean water distribution network of Perumda Air Minum Wae Mbeliling, Lembor District is feasible, because there is a proven return on investment. from the BEP value for 1 year.